Energy economics - Schwarz, Peter M. (Peter Martin) (Textbooks in environmental and agricultural economics, 2023)
"Energy Economics outlines the fundamental issues and possible solutions to the challenges of energy production and use, presenting a framework for decisions based upon sound economic analysis. This approach considers market forces and policy goals, including economic prosperity, environmental protection, and societal well-being. The second edition has been thoroughly updated, addressing dramatic shifts in the use of fuel and electricity, accelerated plans for the use of renewable energy, and pathways towards a lower-carbon future. A new chapter on electric vehicles examines its impact on transportation, the electricity market and carbon emissions. Global examples throughout the book reflect the universal application of energy economics. This economic foundation, coupled with perspectives from real-world applications, and perspectives from related disciplines, this text sharpens the student's ability to understand, evaluate and critique energy policy. A companion website provides reinforcement for students through multiple choice self-test quizzes and homework exercises, as well as additional materials for instructors. This textbook should be essential reading for students of energy economics, environmental and natural resource economics, energy-related disciplines, and general readers seeking to expand their knowledge of energy economics and policy"--